Determinants of organic food purchase intention among Malaysian consumers / Azyanee Luqman...[et al.] - Luqman, Azyanee; Mohd Fazuri, Rosfazira; Zulqernain, Nurul Syaqirah; Mohamad, Siti Sarah; Mohd Fauzi, Mas Ayu Diana (Universiti Teknologi MARA Cawangan Kelantan, 2020)
Recent report revealed that the demand for organic food in Malaysia was small and most of the organic products in the market were imported. This has made it difficult for the local organic food producers to market their products to the local consumers. Hence, this paper aims to identify the factors influencing intention to purchase organic food among Malaysian consumers which are acceptability, affordability, awareness and consumer innovativeness. Data were collected from 100 respondents from an East Coast state in Malaysia using convenience sampling. Subsequently, the data were analysed using SPSS. The multiple regression analysis result shows that acceptability and awareness were found to be significantly related to organic food purchase intention, explaining 53.1% of the variance. On the other hand, affordability and consumer innovativeness were not significant. Finally, the similar and contradict findings to the present study are discussed as well as marketing strategies for local organic food producers and marketers to ensure consumers’ acceptance and awareness are also highlighted